PERSONAL DATA PROTECTION AND ITS REGULATORY FRAMEWORKS UNDER CYBER LAW - Utami, Sal Sabila Khoirotunnisa (Faculty of Law Atma Jaya Yogyakarta University, 2024)
The purpose of this research is to evaluate the effectiveness of personal data protection legislation and raise awareness among the broader community about the importance of safeguarding personal data against cybercrimes. This study employs a normative juridical approach, focusing on library research that examines secondary data and laws governing personal data protection. Additionally, the research adopts a qualitative methodology to provide an in-depth understanding of societal issues related to personal data protection by presenting findings narratively. The results indicate that personal data protection is explicitly addressed in Law No. 27 of 2022, which strengthens regulatory clarity and enforces stricter actions against violations compared to previous legal frameworks. Evidence suggests that the effectiveness of personal data protection laws has improved, as demonstrated by an increasing number of cases resolved comprehensively. Furthermore, individual preventive measures, such as vigilance and securing personal data online, are essential in mitigating cybercrimes.